SYNBATIVITY OF THE ANGIOARCHITECTONICS OF THE TONGUE AND GASTROINTESTINAL TRACT MUCOSA IN THE DISORDERS OF HOMOLOGOUS ORGANS - Gevkaliuk, Nataliia; Drevnitska, Roksana (Eastern Ukrainian Medical Journal, 2024)
Background. The pathology of the digestive organs has remained the object of scientific research for many years due to its significant prevalence in various countries of the world and the absence of a downward trend. In addition to symptoms typical for diseases of the digestive organs, there are non-gastrointestinal symptoms. The oral cavity and the gastrointestinal tract are two synbatic ecosystems affected by a number of factors involved in the pathogenesis of gastrointestinal diseases. The objective of the research was to study the morphofunctional state of the vascular bed of the tongue, stomach, and small intestine and the patterns of reconstruction of their microcirculatory bed during experimental gastritis. Methods. The study was conducted on 60 white laboratory non-linear mature male rats with an average body weight of 180–200 g, in which gastritis was simulated. On the 14th day after the development of gastritis, the animals were sacrificed by intraperitoneal overdose of sodium thiopental solution and the material was collected. Obtained replicas of blood vessels, corrosion casts, samples of the native mucous membrane of the tongue were prepared by the generally accepted method of scanning electron microscopy and examined in a scanning electron microscope ("JEOL-25М-Т220А" (Japan)). Results. The study showed that the general angioarchitectonics of the papillae of the tongue were similar to their appearance. On the dorsal surface of the tongue, dense loops of vessels with superficial hemocapillaries were visible, which was similar to the contours of the corresponding papillae of the tongue. The study of the vascular-corrosion cast of the non-glandular part of the mucous membrane of the stomach showed that the network of the microcirculatory bed was similar the contours of its villi. A subpapillary arterial network was visualized, from which blood was supplied to the intrapapillary capillary loops ansae capillares. In the small intestine, the villus artery unbranched went to its apex, where it divided into marginal capillaries, most of which received blood from the central arterial vessel. The method of corrosion casts in experimental gastritis revealed a reactive reorganization of the microcirculatory channel both in the mucous membrane of the tongue and in the mucous membrane of the stomach, which, in addition to a change in shape, spiralization, was characterized by a change in the diameter of hemocapillaries. We demonstrated an isolated capillary loop of ansae capillares intrapapillares of the "straight type" of the conical papilla of the tongue in normal conditions and its transformation into ansae capillares intrapapillares of the "spiral type" in gastritis, as well as spiral twisting of the hemocapillaries of the glandular lamina of the gastric mucosa in gastritis. An identical reconstruction of angioarchitectonics was characteristic of the mucous membrane of the small intestine. Conclusion. The presented material demonstrates the synbativity and angioarchitectonics correspondence to the external structure of the structural elements of the mucous membrane of homologous organs and demonstrates a number of patterns of reactive structural rearrangement of their angioarchitectonics in experimental gastritis